2010
DOI: 10.1111/j.1365-2133.2010.09903.x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasonography assists the differential diagnosis of blue naevi and cutaneous metastases of melanoma

Abstract: Ultrasonography is a reproducible and specific tool that can assist the differential diagnosis between blue naevi and metastases of melanoma. A blue naevus is a homogeneous, hypoechoic, 'dish-shaped' lesion, located in the superficial dermis, whereas metastases of melanoma are 'potato-shaped', hypoechoic, heterogeneous lesions, located in the hypodermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Furthermore, some congenital acral naevi have a homogeneous blue pattern, as reported by Garrido‐Ríos et al . Samimi et al . reported that ultrasonography is a reproducible tool that can assist in the differential diagnosis between blue naevus and melanoma metastases, but there should be a clinical suspicion present.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some congenital acral naevi have a homogeneous blue pattern, as reported by Garrido‐Ríos et al . Samimi et al . reported that ultrasonography is a reproducible tool that can assist in the differential diagnosis between blue naevus and melanoma metastases, but there should be a clinical suspicion present.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of echography may help to differentiate blue nevi from a blue-colored melanoma metastasis, because blue nevi are generally dish-shaped and have a homogeneous echo whereas melanoma metastases are potato-shaped and show an inhomogeneous echo. 36 …”
Section: Metastasismentioning
confidence: 99%
“…Acoustic shadowing and retrolesional echogenicity may assist the diagnosis between benign naevus and melanoma (18) Quantitative discrimination of pigmented lesions seems possible using three-dimensional high-resolution ultrasound reflex transmission imaging (19). Blue naevi are also hypoechoic, and often have a dish shape or an ovoid shape ( Fig.3a and 3b) (20). …”
Section: Ultrasound Imaging Of Naevimentioning
confidence: 99%
“…They are often visible or palpable, and may simulate a benign blue naevus. However, the shape of the lesion is different for a blue naevus and a recurrence of melanoma (20). Moreover, ultrasound examination is able to detect subclinical in transit recurrence in some cases.…”
Section: Ultrasound Imaging Of Local or In Transit Recurrence And Dismentioning
confidence: 99%